Application of the collocation method to the multi-point boundary value problems with integral boundary conditions - Ronto, N.I.; Putyatina, T.V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
An algebraic collocation method for approximating solutions of systems of nonlinear ordinary differential equations is shown to be applicable in the case of linear multipoint boundary conditions containing definite integrals.